Plasmodium falciparum in vitro continuous culture conditions: A comparison of parasite susceptibility and tolerance to anti-malarial drugs throughout the asexual intra-erythrocytic life cycle. Issue 3 (December 2017) - Duffy, Sandra; Avery, Vicky M.
Abstract: The continuous culture of Plasmodium falciparum is often seen as a means to an end, that end being to probe the biology of the parasite in question, and ultimately for many in the malaria drug discovery arena, to identify means of killing the parasite in order to treat malaria. In vitro continuous culture of Plasmodium falciparum is a fundamental requirement when undertaking malaria research where the primary objectives utilise viable parasites of a desired lifecycle stage. This investigation, and resulting data, compared the impact culturing Plasmodium falciparum long term (4 months) in different environmental conditions had on experimental outcomes and thus conclusions. The example presented here focused specifically on the effect culture conditions had on the in vitro tolerance of Plasmodium falciparum to standard anti-malarial drugs, including artemisinin and lumefantrine. Historical data from an independent experiment for 3D7-ALB (5% O2 ) was also compared with that obtained from this study. We concluded that parasites cultured for several months in media supplemented with a serum substitute such as Albumax II ® or within hyperoxic conditions (21% O2 ), demonstrate highly variable responses to artemisinin and lumefantrine but not all anti-malarial drugs, when compared to those cultured in human serum in combination with Albumax II ® under normoxic conditions (5% O2 ) for the parasite. Graphical abstract: Image 1